Technology-Enhanced ESP Instruction: Improving Law Students' Speaking Skills Through Digital Resources - Dewi Surani; Isnaini Eddy Saputro; Amrina Rosyada; Fajar Hayyin (Universitas Muria Kudus, 2026)
This experimental study aimed to examine the effect of digital resources on improving ESP learners' speaking skills. Using purposive sampling, 52 students were selected as participants. Quantitative data were collected through pretests and posttests and analyzed using a paired-samples t-test, which revealed a significant improvement from the pretest mean score (M = 57.11) to the posttest mean score (M = 67.26), t(51) = 22.67, p < .00. The statistical results revealed a significant difference between pretest and posttest scores, indicating that the use of digital resources as pre-class material effectively enhanced students' speaking abilities. Qualitative findings from semi-structured interviews further indicated that students perceived the digital resources as supportive, motivating, and helpful in reducing speaking anxiety. These findings suggest that integrating technology through digital resources can foster a more supportive and interactive learning environment, ultimately promoting greater speaking proficiency among ESP learners.